2018
DOI: 10.1111/efp.12411
|View full text |Cite
|
Sign up to set email alerts
|

First detection of Neoscytalidium dimidiatum associated with canker disease in Egyptian Ficus trees

Abstract: In September 2013, a canker disease of Ficus nitida and F. benjamina was reported for the first time in Assiut governorate, Egypt. Infected samples were collected from various locations. Pure cultures of a fungus were isolated on potato dextrose agar at 25°C from diseased plants. Morphological investigation and DNA sequencing showed that the causal agent was Neoscytalidium dimidiatum. A pathogenicity test conducted using 2-year-old plants of each host gave 70%-80% infection, and the pathogen was reisolated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
(41 reference statements)
3
12
0
Order By: Relevance
“…For that reason, phylogenetic analysis using TEF1-α sequence (MN447201) was generated and proved the identity of the fungus as N. dimidiatum. N. dimidiatum was closely related to both N. novaehollandiae [33] and N. hyalinum [34], confirming previous findings [13,35]. Our data indicated that the isolate of N. dimidiatum in the current study was morphologically and genetically similar to other isolates of N. dimidiatum from Juglan regia, Prunus sp., mango and others.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…For that reason, phylogenetic analysis using TEF1-α sequence (MN447201) was generated and proved the identity of the fungus as N. dimidiatum. N. dimidiatum was closely related to both N. novaehollandiae [33] and N. hyalinum [34], confirming previous findings [13,35]. Our data indicated that the isolate of N. dimidiatum in the current study was morphologically and genetically similar to other isolates of N. dimidiatum from Juglan regia, Prunus sp., mango and others.…”
Section: Discussionsupporting
confidence: 91%
“…The results obtained from the greenhouse experiment on young healthy plants after inoculation were similar to the disease symptoms on trees of royal poinciana located in the field, and that was confirmed by Koch's postulates when N. dimidiatum was frequently recovered from the inoculated seedlings. Our data match those in other trials using artificial inoculation of the same pathogen on royal poinciana [16] or other plant species [13][14][15]20,28]. Pathogenicity assays on seedlings of royal poinciana (Figure 4), F. benjamina and F. nitida [13] and eucalyptus, poplar and olive [30] clearly described that discoloration of vascular tissues, and drying and defoliation of leaves, were symptoms associated with stem canker caused by N. dimidiatum.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations